Anionic Magnesium and Calcium Hydrides: Transforming CO into Unsaturated Disilyl Ethers. (30th November 2022) - McMullen, Jacob S.; Huo, Ryan; Vasko, Petra; Edwards, Alison J.; Hicks, Jamie
Abstract: The synthesis, characterisation and reactivity of two isostructural anionic magnesium and calcium complexes is reported. By X‐ray and neutron diffraction techniques, the anionic hydrides are shown to exist as dimers, held together by a range of interactions between the two anions and two bridging potassium cations. Unlike the vast proportion of previously reported dimeric group 2 hydrides, which have hydrides that bridge two group 2 centres, here the hydrides are shown to be "terminal", but stabilised by interactions with the potassium cations. Both anionic hydrides were found to insert and couple CO under mild reaction conditions to give the corresponding group 2 cis ‐ethenediolate complexes. These cis ‐ethenediolate complexes were found to undergo salt elimination reactions with silyl chlorides, allowing access to small unsaturated disilyl ethers with a high percentage of their mass originating from the C1 source CO. Abstract : CO has directly been transformed into small organic starting materials using earth‐abundant, anionic group 2 hydride reagents.